Perceived motivators, knowledge, attitude, self-reported and intentional practice of female condom use among female students in higher training institutions in Dodoma, Tanzania - Getrude W. Shitindi; Walter C. Millanzi; Patricia Z. Herman (BMC, 2023)
Abstract Background Unplanned pregnancies and sexually transmitted infections (STIs) Human Immunodeficiency Virus (HIV) inclusive, have remained to be a significant public health challenges among young people, especially across middle and low-income countries. Self-efficacy on the right ways of using condoms appears to be effective against the aforementioned health-related problems. However, most women of reproductive age tend not to use them when they are using highly effective contraceptives such as implants, and/or injectable hormones. It is unknown whether the uptake of female condoms among young girls is significantly high or not. Examining female students' perceived motivators, knowledge, attitudes, and self-reported and intentional female condom practice in training institutions seems to be a key precursor in addressing the challenge. Methods The institutional-based analytical cross-sectional survey in a quantitative research approach was adopted to study 384 randomly selected female students from higher training institutions, in Tanzania. Interviewer-administered structured questionnaires from previous studies were the main data collection tools. Data analysis was done using a statistical package for social science (SPSS) with the strength of statistical limits set at a 95% confidence interval and a 5% significance level. Results The response rate of the study was 100% with 24 ± 2.122 years respondents' mean age while and 32.7% of them were in the third year of their studies. Only 6.2% of the respondents reported having used female condoms while 26.3% of them have not ever seen packages of female condoms. The minority of the respondents (21.7%, 23.3%, and 9.4%) demonstrated good knowledge, positive attitude, and intention to use female condoms respectively. Their age, accommodation, marital status, peer groups, previous training, knowledge, and attitude related significantly to their intentional practices of female condom use (p < 0.05). Conclusion Given the existing governmental and non-governmental efforts that advocate awareness creation and the uptake of various contraceptives, this study has found that knowledge, attitude, self-reported and intentional practices of female students admitted in higher training institutions within Dodoma region, Tanzania is low. Institutionalized educational programs on sexual and reproductive health matters may need to be prioritized to increase the availability, accessibility, and uptake of female condoms among female students in higher training institutions.